Note from the founding editor: 10 years after (Colloquia Comparativa Litterarum, 2025)
In the first letter "From the Editor" of Colloquia Comparativa Litterarum from 2015, I happily wrote that you can “scroll down the pages of the new journal”. It was a freshly created online academic journal with double-review and free access. Now it continues developing in close proximity with the Balkan Studies Master’s and Doctoral Degree Programme within the Faculty for Slavic Studies of Sofia University St. Kliment Ohridski. Colloquia Comparativa Litterarum has already become known and indexed in Bulgaria and widely around the world: on the National Reference List of Modern Bulgarian Peer-Reviewed Academic Publications, in CEEOL (Central and Eastern European Online Library), in MLA International Bibliography and in EBSCO Information Services. We have also submitted the journal to the attention of Web of Science and are awaiting its inclusion.Today, in 2024, 10 years after publishing regularly a new issue every July 1 each year, the Editorial Board of Colloquia Comparativa Litterarum and myself are satisfied with the opportunity to develop further the research in the field of Comparative Literature and Balkan Studies. The three languages adopted by the journal, the local Bulgarian, as well as the traditional languages of our discipline, French and English, allow us to pursue this goal.For every next issue we continue to invite colleagues from Bulgaria and all over the world to contribute on pertinent topics of our time: in the year 2024 disrupted by international conflicts, Dystopia emerged as a characteristic literary theme. Throughout the past ten years, some of the more impressive themes have been Pars pro toto. The Literary Balkans in Europe (in 2017), The Creation of the World: God, Genius, Woman (2019), The Solitary Walker – Introspection аnd Revolt (suited for the Covid-year 2021), in 2023 – Forms and Modes of Empathy: Heroes and Anti-Heroes in a Comparative Perspective. We keep as permanent the sections: Miscellanea and Book Reviews. Almost every year we run an editorial internship programme for our Master’s degree and PhD students.The colleagues from the Bulgarian and the International Editorial Boards of Colloquia Comparativa Litterarum – https://ejournal.uni-sofia.bg/index.php/Colloquia/about/editorialTeam -each with their own professional profile form a team that supports comparative issues and contributes personally to the specific nature of the journal. This is the place to remember those who are no longer with us: Associate Professor Dimitar Birov, PhD (1962–2019) – the first IT Support person of the journal, and the young and talented literary critic Sirma Danova, PhD (1984–2023).Comparative work constantly reminds us that literature breathes the same air as the other forms of art, and therefore each journal cover displays an artistic image. Since 2020, we have been deliberately inviting contemporary Bulgarian artists and presenting them in the respective issue, and we are happy with this consonance of ideas. Thus, the artists Medea Yankova, Tatiana Harizanova (who also became our artistic consultant), Ventzislav Dikov, Ivan Shishkov and Styliana Uzunova have accompanied us with their imagination and talent.Therefore, with its 10th issue, the journal Colloquia Comparativa Litterarum continues its literary adventure…